(untitled) (Journal of Asian Development Studies, 2024)
The 21st century’s climate change has become an eminent threat to humanity, the cosmos and the earth. Homo sapiens, in their pursuit to achieve the quality of life, have conducted irreversible and irreparable damage to the habitat as the good environment of it. This study comprehensively and extensively analyses Arundhati Roy’s The God of Small Things (1997). She gives a detailed account of nature in her novel and describes nature in the present and past scenarios. The study will be based on the theoreticalframework of ecocriticism (Garrad, 2004). The ecocritical theory explicitly looks into the relationship between literature and the physical environment in terms of their influence on each other (Glotfelty,1996). This paper represents how Arundhati Roy haspresented her concern for the environment, which human beings have mercilessly misused in the garb of civilization, development and modernization. It also highlights how the deteriorated and detrimental effect of human exploitation of nature directly affects the environment and living space.